Control of unstable systems - Sree, R. Padma (Alpha Science, 2006)
Coverage on computers and principles in designing digital controllers Details on computer networking, topology, communication protocol, and DCS Fundamentals of fuzzy logic control, their design and use of fuzzy logic in improving performance of conventional PID controllers presented Several case studies provided to illustrate the design of digital controllers